Inflammatory myofibroblastic tumor with ROS1 gene fusions in children and young adolescents - Schoot, Reineke A.; Orbach, Daniel; Minard Colin, Veronique; Alaggio, Rita; Di Carlo, Daniela; Corradini, Nadege; Mercolini, Federico; Milano, Giuseppe Maria; van Noesel, Max M.; Rome, Angelique; Dall’Igna, Patrizia; Pajtler, Kristian Wilfried; et al. (JCO precision oncology, 2023)
Purpose - Inflammatory myofibroblastic tumors (IMTs) are often driven by anaplastic lymphoma kinase fusions and less frequently by alternative fusions such as ROS1. We describe the clinical characteristics, treatment approach, and outcome for a series of young patients with IMTs and ROS1 alterations. - Methods - This was a retrospective, international, multicenter study analyzing young patients (younger than 21 years) with ROS1-altered IMTs treated in 10 European referral centers between 2014 and 2022. Patients were included in the European pediatric Soft tissue sarcoma Study Group NRSTS-2005 protocol or registered in the Soft Tissue Sarcoma Registry. Primary surgery was recommended if a microscopic radical resection was feasible without mutilation. No standard systemic treatment protocol was available, but several medical options were recommended. - Results - A total of 19 patients (median age 8.3 years) were included. Most patients had a biopsy at diagnosis (Intergroup Rhabdomyosarcoma Study [IRS] I; n = 2, IRS II; n = 1, IRS III biopsy; n = 11, IRS III resection; n = 3, IRS IV; n = 2). Twelve patients received neoadjuvant systemic therapy in first line (four received multiple treatments): high-dose steroids (n = 2), vinorelbine/vinblastine with methotrexate (n = 6), or ROS1 inhibitors (n = 8). After a median follow-up of 2.8 years (range, 0.2-13.4), seven patients developed an event. The 3-year event-free survival was 41% (95% CI, 11 to 71), and the 3-year overall survival was 100%. - Conclusion - Outcome for ROS1-altered IMTs appears excellent. A complete resection at diagnosis was often not feasible, and most patients needed neoadjuvant therapy. Patients who developed a tumor event could be cured with reinitiation of systemic therapy and/or surgery. This approach illustrates a switch in treatment philosophy moving from immediate, often mutilating, surgery to systemic (targeted) therapy as a bridge to more conservative surgery later in the treatment course.
Gesehen am 28.01.2025